Prosedur Pelayanan Pengurusan KTP Elektronik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Minahasa - Christi Jovanca Madi; Jeane Elisabeth Langkai; Steven Tarore; Diza Ramadhani S (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
The purpose of this study is to find out the service procedures for managing electronic KTPs at the Population and Civil Registration Office of Minahasa Regency which have not been maximized. The approach used in this research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. The data analysis used is data collection, data condensation, data presentation and conclusion. The results of this study indicate that judging from the KTP-Electronic service procedures at the Population and Civil Registration Office of Minahasa Regency, it can be seen from several indicators, namely, 1) Procedures for Submitting Applications, this indicator found that there are still obstacles to the lack of providing information regarding the flow of submissions and information regarding requirements. 2) Procedures for Handling The services provided by the agency are good enough where the employees in charge of providing services are careful enough in providing the existing services. 3) The method of delivering service results where in this indicator it is found that the delivery of results carried out is not in accordance with the existing SOP where there is still no certainty of the time given by the agency as a service provider, this is due to constraints on available facilities and infrastructure